Driving Green: Economic Policies Fuelling Sustainable Mobility and Future Prospects in Poland - Jankowska-Karpa, Dagmara; Wnuk, Aneta (Cognitive Sustainability, 2024)
Poland is actively implementing economic policies to promote sustainable mobility, driven by the need to align with European Union (EU) directives and improve environmental sustainability. This paper aims to provide a comprehensive overview of these policies, focusing on emission standards, technology standards, performance standards and the use of taxes and subsidies. Data and methods include reviewing legislative documents, policy analysis and case studies from major Polish cities. The results indicate considerable progress in reducing emissions, promoting electric vehicles (EVs) and improving public transport infrastructure. However, challenges such as excessive costs and infrastructure constraints remain. The conclusion highlights the importance of continuous policy development and investments in sustainable technologies to achieve long-term environmental goals.